PARADIGMA DAN PENGATURAN PENGELOLAAN SUMBER DAYA AIR PASCA LAHIRNYA UNDANG UNDANG NOMOR 17 TAHUN 2019 - Wahyu Fahmi Rizaldy (Journal of Law and Administrative Science, 2023)
Management and utilization of water resources will increase along with the rate of population growth, increasing living standards and regional economic growth. Human needs for water in life generally consist of clean water needs, agricultural water needs and industrial water needs. Provisions for water use permits in Law no. 17 of 2019 which is not regulated in PP No. 69 of 2014, namely permission to use water to meet needs for activities other than meeting basic daily needs and people's agriculture which is not a business activity, it can be said that PP No. 69 of 2014 is no longer in accordance with the provisions in Law no. 17 of 2019 so that it needs to be revoked and new government regulations formed as implementing regulations for Law no. 17 of 2019. The paradigm that will be built with the enactment of Law Number 17 of 2019 is to improve the previous paradigm which was not in line with people's expectations so that there would be no leap in the authority to manage water resources in the hope that a more effective and efficient resource management system would be realized..